2021
DOI: 10.1080/09638288.2021.1979109
|View full text |Cite
|
Sign up to set email alerts
|

Content and psychometric evaluations of questionnaires for assessing physical function in people with arm–shoulder–hand disorders. A systematic review of the literature

Abstract: Florin (2021): Content and psychometric evaluations of questionnaires for assessing physical function in people with arm-shoulder-hand disorders. A systematic review of the literature, Disability and Rehabilitation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The DASH is a tool for evaluating hand function status, disability, and symptoms and has been used extensively in interventional research to evaluate functional outcomes following hand burns. Although physical function is better measured by healthcare professionals through physical examination and observation, in their systematic review, Wiitavaara and Florin (2022) stated that the DASH, a patient-reported outcome measure, represents ADLs and gross motor tasks and performance, which is a practical way to assess physical function. After the intervention in the present study, patients had lower DASH mean scores (mean = −27 points); a 10-point difference in DASH mean score reflected a minimally significant clinical change, according to Gummesson et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DASH is a tool for evaluating hand function status, disability, and symptoms and has been used extensively in interventional research to evaluate functional outcomes following hand burns. Although physical function is better measured by healthcare professionals through physical examination and observation, in their systematic review, Wiitavaara and Florin (2022) stated that the DASH, a patient-reported outcome measure, represents ADLs and gross motor tasks and performance, which is a practical way to assess physical function. After the intervention in the present study, patients had lower DASH mean scores (mean = −27 points); a 10-point difference in DASH mean score reflected a minimally significant clinical change, according to Gummesson et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, more research is needed to determine the validity of the self-reported DASH as a functional outcome predictor in patients with burns, as well as to create or validate existing objective hand functional outcome instruments. Outcome measurement has evolved into a tool for describing, monitoring, reporting, and evaluating the effects of health interventions on patients (Wiitavaara & Florin, 2022). Nurses will be able to improve the early and long-term rehabilitation process, not just the outcomes, by measuring functional outcomes for patients with burns (Wiitavaara & Florin, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain questionnaires focused on carrying out daily activities and pain, such as the DASH, the QuickDASH and the PWRE questionnaire (41,42,44), while others included emotional aspects related to postoperative recoveries, such as SFMA, the Global QoR-40K and the EQ-ED-3L (43,46,51). Consequently, it is challenging to compare the score obtained from various questionnaires and the functional recovery may not be generalizable between studies due to the lack of standardization in the eld (52).…”
Section: Discussionmentioning
confidence: 99%
“…The patient self-report measures included the following: 1) Numerical Pain Rating Scale (NPRS); 2) Global Perceived Effect (GPE) or Global Rating of Change (GROC) scale; and 3) Neck Disability Index (NDI) or the Quick-Disabilities of the Arm, Shoulder, and Hand (QuickDASH). These are valid measures with established minimum detectable change (MDC) and minimum clinically important differences (MCID) [13][14][15][16][17]. Statistically significant change in these has been reported as a change of +/-2/10 on NPRS, +/-5 points on GROC, 19% on NDI, and 15% on QuickDASH [13][14][15]17,18].…”
Section: Figure 1: Cervical Flexion Rotation Test Figure 2: Cervical ...mentioning
confidence: 99%